Development of Students-Speech Therapists’ Professional Competences in the Frameworks of Informational and Educational Environment of University - Elena Shilova; Gulnara Valiulina; Emiliano Mettini (ARPHA Proceedings, 2019)
The relevance of study issue reflects the search of technological resources promoting an effective development of student speech therapists’ professional competences in the field of diagnostic and corrective-developing activities. Implementation of developing competence model implies the use of differentiated approaches in teaching, the combination of traditional methods and innovative technological working outs. Authors’ electronic program as a way for training skills that are needed in solving pedagogical diagnostic and corrective-developing tasks is regarded as one of didactic resources in informational-educational environment of University. The goal of the present paper is analyzing the effective use of author’s electronic program in training teachers-speech therapists for forming diagnostic and correctional-developing competences. In this case the main research method is the competent approach aimed at productive use of integrated knowledge in practice, promoting creative capacities and self-development of graduates, thereby implementing the development of students-speech therapist’s professional competences through the resolution of pedagogical tasks, using electronic resources. Research highlighted difficulties and "problem areas" at each level of competences development (knowledge, skills, and abilities) while elaborating diagnostic and correctional-developing program of competences. Analysis of results permits the elaboration of an electronic didactical resource which is based on algorithms of multidisciplinary tasks aimed at development of professional skills and abilities in the field of special training and education. The importance of research results for practice is confirmed by the fact that they are directly focused on resolution of pressing challenges concerning the development of students-speech therapists’ professional competences, and they may effectively develop such competences in the frameworks of University informational-educational environment.